2009
DOI: 10.1161/circheartfailure.109.852228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Extensive Transverse Tubular Network in Sheep Atrial Myocytes and its Depletion in Heart Failure

Abstract: Background-In ventricular myocytes, the majority of structures that couple excitation to the systolic rise of Ca 2ϩ are located at the transverse tubular (t-tubule) membrane. In the failing ventricle, disorganization of t-tubules disrupts excitation contraction coupling. The t-tubule membrane is virtually absent in the atria of small mammals resulting in spatiotemporally distinct profiles of intracellular Ca 2ϩ release on stimulation in atrial and ventricular cells. The aims of this study were to determine (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
201
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(227 citation statements)
references
References 30 publications
(37 reference statements)
26
201
0
Order By: Relevance
“…Recent work in human right atrial tissue has shown the presence of TTs, albeit less abundant than in other large mammals (cow, horse, sheep) (33). A denser TT system leads to more DHPR-RyR2 pairs at the junctional SR (jSR), thus facilitating (near-) simultaneous CaT activation throughout the cell (34). In the present study, ss and cc CaT amplitudes were the same in CTL cells.…”
Section: Discussionsupporting
confidence: 40%
“…Recent work in human right atrial tissue has shown the presence of TTs, albeit less abundant than in other large mammals (cow, horse, sheep) (33). A denser TT system leads to more DHPR-RyR2 pairs at the junctional SR (jSR), thus facilitating (near-) simultaneous CaT activation throughout the cell (34). In the present study, ss and cc CaT amplitudes were the same in CTL cells.…”
Section: Discussionsupporting
confidence: 40%
“…Evidence from animal models of heart diseases that predispose to AF indicates that disease-associated remodeling of the atria, presumably due to mechanical overload of the atrial wall, creates an arrhythmic substrate in which AF is more likely to arise and be sustained (10,13,22,29,30,32,34,48). In addition to atrial enlargement, fibrosis and conduction abnormalities that establish a substrate for reentry, cellular remodeling involving cellular hypertrophy, changes in membrane structure, and abnormal expression and function of ion channels and transporters are also likely to contribute to the genesis of AF (4,10,13,15,16,18,22,26,29,30,32,34,35,38,48,51).…”
Section: New and Noteworthy Whole Cell Recording Of L-type Ca 2ϩmentioning
confidence: 99%
“…Evidence from animal models of heart diseases that predispose to AF indicates that disease-associated remodeling of the atria, presumably due to mechanical overload of the atrial wall, creates an arrhythmic substrate in which AF is more likely to arise and be sustained (10,13,22,29,30,32,34,48). In addition to atrial enlargement, fibrosis and conduction abnormalities that establish a substrate for reentry, cellular remodeling involving cellular hypertrophy, changes in membrane structure, and abnormal expression and function of ion channels and transporters are also likely to contribute to the genesis of AF (4,10,13,15,16,18,22,26,29,30,32,34,35,38,48,51).Atrial L-type Ca 2ϩ current (I CaL ) is reduced in heart disease, both in animal models (4,13,29,38) and in myocytes from human dilated atria (19,33). The loss of I CaL has been suggested to have a number of sequelae that contribute to the genesis of AF, including 1) changes in action potential configuration and the rate dependence of refractoriness, 2) abnormalities in Ca 2ϩ handling and the triggering of episodes of AF, and 3) hypocontractility and dilatation of the atria (15,29,33,35,42).…”
mentioning
confidence: 99%
“…Furthermore, immunohistochemistry suggests the presence of t tubules in the cow atria (34). In sheep, atrial cell-triggered Ca 2ϩ release occurs simultaneously at the cell center and periphery (11), and in the dog atria Ca 2ϩ signals are similar in subsarcolemmal and central regions (43). In the rat atrium, the rudimentary t-tubule system is more apparent in larger diameter myocytes (25,40) consistent with the hypothesis that atrial myocytes with a comparatively large width require t tubules to allow rapid propagation of the Ca 2ϩ transient to the cell interior.…”
mentioning
confidence: 99%